Comparative field efficacy of all-in-one intradermal vaccine based on an inactivated recombinant Mycoplasma hyopneumoniae with an embedded/integrated porcine circovirus type 2 (PCV2) capsid protein and concurrent administration with monovalent of M. hyopneumoniae and PCV2 intradermal vaccine - Suh, Jeongmin; Ham, Sehyeong; Chae, Chanhee (Frontiers in Veterinary Science, 2025)
BackgroundEfficacy of an intradermal all-in-one vaccine based on an inactivated recombinant Mycoplasma hyopneumoniae strain with an embedded/integrated porcine circovirus type 2 (PCV2) capsid protein thereof, as the single active substance, is provided.ObjectiveTo evaluate and compare an intradermal M. hyopneumoniae and PCV2 all-in-one vaccine with monovalent of M. hyopneumoniae and PCV2 intradermal vaccines administered concurrently.AnimalsA total of 60 pigs were randomly divided into three groups (20 pigs per group; male =10 and female = 10) in each of three farms.MethodsThe clinical field trials were conducted on three farms, each suffering from PCV2 infection and enzootic pneumonia. The pigs in the all-in-one-vaccinated groups were injected intradermally with 0.2 mL of the all-in-one vaccine through a needle-free device. The pigs in the concurrent-vaccinated groups were injected with 0.2 mL of PCV2 vaccine and 0.2 mL of M. hyopneumoniae vaccine intradermally through a needle-free device, which allows two vaccines each in their separate vials to be applied simultaneously. The pigs in the unvaccinated groups were administered an equal volume of phosphate buffered saline in the same manner at 21 days of age.ResultsIntradermal vaccination improved pig production performance. It was also able to stimulate systemic humoral and cell-mediated immune responses to M. hyopneumoniae and PCV2d, which reduced M. hyopneumoniae nasal loads and the severity of mycoplasmal lung lesions. Through this stimulation, PCV2 blood viral load and lymphoid severity were also reduced.DiscussionThe intradermal vaccines were considered efficacious and conferred cross-protection of pig herds suffering from PCV2 infection and enzootic pneumonia.